2020
DOI: 10.15446/esrj.v24n3.77670
|View full text |Cite
|
Sign up to set email alerts
|

Trend characteristics of rainy days and evaporation at a tropical rainforest region in East Malaysia, Borneo

Abstract: Impact of climate change over the hydrological system in a region can be identified through statistical characterization of hydrometerological parameters such as rainfall, temperature, humidity and evaporation. In order to understand the influence of climate change, statistical trend characteristics of rainy days, non-rainy days and evaporation rate in the Limbang River Basin (LRB) in Sarawak, Malaysia, Northern Borneo was assessed in the present research. Annual rainfall and monthly evaporation data, over a p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 98 publications
(98 reference statements)
0
1
0
Order By: Relevance
“…The study concluded that the relative impact of climate change was greater than that of human activities. Krishnan et al [19] investigated the effect of climate change on evaporation rates in the Limbang River Basin of Sarawak, Malaysia. The results revealed an overall increasing trend in monthly evaporation rates.…”
Section: Introductionmentioning
confidence: 99%
“…The study concluded that the relative impact of climate change was greater than that of human activities. Krishnan et al [19] investigated the effect of climate change on evaporation rates in the Limbang River Basin of Sarawak, Malaysia. The results revealed an overall increasing trend in monthly evaporation rates.…”
Section: Introductionmentioning
confidence: 99%